Ultrastructure of the gland responsible for the synthesis of an aggregation pheromone in Rhynchophorus palmarum (L.) (Coleoptera: Curculionidae) - Sánchez, Pedro A.; Sánchez, Fredi; Jaffé, Klaus; Caetano, Flavio H. [UNESP] (My University, 1998)
The ultrastructure of the glands responsible for synthesizing the aggregation pheromone rhynchophorol in the beetle Rhynchophorus palmarum (L.) was studied. Glands from live beetles were removed and examined under a light microscope using semithin sections (∼1μm) and under a transmission electron microscope (TEM) using ultrathin sections (60 nm). The glands show an alveolar structure without a reservoir and the cells making up the gland are arranged in a typical acinus pattern. The existence of two types of cells with different electron densities, secretion canaliculi, numerous mitochondria and smooth endoplasmic reticulum in abundance were observed. These latter organelles are characteristic of cells which synthetize non-proteinaceous substances and are thus, likely candidates for the producion of rhynchophorol.